(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Learning mathematics so far still shows relatively low results. This is due, among others, to the strategy, model, technique and approach used is monotonous. This study aims to see the effect of a realistic mathematics learning approach on mathematics learning outcomes . As subjects in this PTK were class VII students at SMP Negeri 13 Gorontalo. Students in these subjects are considered to have problems in congruence material. This is shown by the results of previous observations.The data collection tool used is the instrument of observation and analysis of the results of daily tests .The data analysis technique used is a qualitative analysis taken from observational data from Cycle 1 to Cycle 2 which are converted to table l qualifications, then to table l daily returns. Testing the Classroom Action Research (PTK) hypothesis is based on the results of observations through action cycles during the learning process and the results of daily tests.This research produced two findings namely: (1) overall learning achievement can be increased in the learning process. This is indicated by an increase in the score obtained from observations and the qualification of the assessment component " good enough" to "good and very good" or from category C to categories B and A. (2) Realistic learning will be able to improve learning outcomes on congruence material.